COP1 Deficiency in BRAFV600E Melanomas Confers Resistance to Inhibitors of the MAPK Pathway - Ada Ndoja; Christopher M. Rose; Eva Lin; Rohit Reja; Jelena Petrovic; Sarah Kummerfeld; Andrew Blair; Helen Rizos; Zora Modrusan; Scott Martin; Donald S. Kirkpatrick; Amy Heidersbach; et al. (Cells)
Aberrant activation of the mitogen-activated protein kinase (MAPK) cascade promotes oncogenic transcriptomes. Despite efforts to inhibit oncogenic kinases, such as BRAFV600E, tumor responses in patients can be heterogeneous and limited by drug resistance mechanisms. Here, we describe patient tumors that acquired COP1 or DET1 mutations after treatment with the BRAFV600E inhibitor vemurafenib. COP1 and DET1 constitute the substrate adaptor of the E3 ubiquitin ligase CRL4COP1/DET1, which targets transcription factors, including ETV1, ETV4, and ETV5, for proteasomal degradation. MAPK-MEK-ERK signaling prevents CRL4COP1/DET1 from ubiquitinating ETV1, ETV4, and ETV5, but the mechanistic details are still being elucidated. We found that patient mutations in COP1 or DET1 inactivated CRL4COP1/DET1 in melanoma cells, stabilized ETV1, ETV4, and ETV5, and conferred resistance to inhibitors of the MAPK pathway. ETV5, in particular, enhanced cell survival and was found to promote the expression of the pro-survival gene BCL2A1. Indeed, the deletion of pro-survival BCL2A1 re-sensitized COP1 mutant cells to vemurafenib treatment. These observations indicate that the post-translational regulation of ETV5 by CRL4COP1/DET1 modulates transcriptional outputs in ERK-dependent cancers, and its inactivation contributes to therapeutic resistance.